West Bank and Gaza : Country Procurement Issues Paper - World Bank (Washington, DC, 2013)
The main aim of the CPIP is to assess the current state of pubic procurement in West Bank and Gaza in the form of a ''snap shot'' and accordingly, to provide a partial assessment, broadly along the lines of the OPCS paper that would address the following objectives. First, to assess the latest progress with regard to the procurement reform recommended by the 2004 CPAR and the commitment of the Palestinian Authority (PA) to pursue the reform. Next, to report on the link between public sector procurement and the local private sector, in terms of competitiveness, performance, constraints, and commercial practices affecting public procurement. Finally, compile a set of recommendations that would strengthenprocurement arrangements and functions under future Bank-financed operations in the WB&G. These could also serve as basis to suggest specific improvements in current procurement processes, as well as next steps towards the achievement of a procurement system that meets internationally recognized standards.